VERBAL AND NONVERBAL COMMUNICATION PATTERNS IN THE CATCALLING PHENOMENON IN THE UNIVERSITY OF NORTH SUMATERA - Tanya Chynta Wulandari Alamsyah; Hotmatua Paralihan (Journal Analytica Islamica, 2026)
The phenomenon of catcalling remains common in campus interactions and appears through direct verbal and nonverbal communication without personal relationships or consent from the recipient. This study aims to analyze verbal and nonverbal communication patterns in the catcalling phenomenon at the University of North Sumatra by using the Stimulus–Organism–Response (S-O-R) theory as an analytical framework. This study employed a descriptive qualitative method through in-depth interviews with female students who had experienced catcalling on campus. The findings show that verbal communication patterns appear through calls, comments, and seductive expressions such as “beautiful,” “dear,” “sst beautiful,” and “smile, please.” Nonverbal communication patterns are shown through intense stares, whistles, smiles, and body gestures directed at victims. These forms of communication function as stimulus that triggers internal psychological processing among victims, including discomfort, fear, and vigilance. The responses that emerge include silence, ignoring the perpetrator, avoiding eye contact, and leaving the location. The theoretical contribution of this study lies in explaining catcalling as a patterned interpersonal communication process in which verbal and nonverbal messages operate as stimulus, victims’ emotional and cognitive experiences function as organism, and defensive actions appear as response. Thus, catcalling is not merely a spontaneous act, but a repeated communication pattern shaped by verbal expressions, nonverbal cues, and interactional situations in campus spaces.